2017
DOI: 10.1016/j.celrep.2016.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Acetate Recapturing by Nuclear Acetyl-CoA Synthetase 2 Prevents Loss of Histone Acetylation during Oxygen and Serum Limitation

Abstract: SummaryAcetyl-CoA is a key metabolic intermediate with an important role in transcriptional regulation. The nuclear-cytosolic acetyl-CoA synthetase 2 (ACSS2) was found to sustain the growth of hypoxic tumor cells. It generates acetyl-CoA from acetate, but exactly which pathways it supports is not fully understood. Here, quantitative analysis of acetate metabolism reveals that ACSS2 fulfills distinct functions depending on its cellular location. Exogenous acetate uptake is controlled by expression of both ACSS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
205
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(223 citation statements)
references
References 32 publications
(65 reference statements)
9
205
0
1
Order By: Relevance
“…5g and 5h) and isotope tracing with deuterated acetaldehyde confirmed that ACLY knockdown cells exhibited increased acetate utilization which could be further increased by limiting nutrient availability during serum starvation (Fig. 5i), which is consistent with previous findings 10,34 . Thus these experiments confirm that de novo pyruvate-derived acetate production can have critical functional roles in supporting acetyl-CoA metabolism.…”
Section: Resultssupporting
confidence: 91%
“…5g and 5h) and isotope tracing with deuterated acetaldehyde confirmed that ACLY knockdown cells exhibited increased acetate utilization which could be further increased by limiting nutrient availability during serum starvation (Fig. 5i), which is consistent with previous findings 10,34 . Thus these experiments confirm that de novo pyruvate-derived acetate production can have critical functional roles in supporting acetyl-CoA metabolism.…”
Section: Resultssupporting
confidence: 91%
“…Acetate can rescue global histone acetylation in the absence of ACLY (Wellen et al, 2009; Zhao et al, 2016), though use of exogenous acetate for histone acetylation is somewhat inefficient (Bulusu et al, 2017; Zhao et al, 2016), suggesting that ACLY- and ACSS2-generated acetyl-CoA might be differentially used in specific contexts. Silencing of ACSS2 had no significant impact on BRCA1 foci formation (Figure S2F).…”
Section: Resultsmentioning
confidence: 99%
“…ACSS2 is essential for protein acetylation by producing acetyl CoA, which has an important role in many biological processes. ACSS2 can increase histone H3 acetylation in specific regions, which is vital to autophagy, cell survival and tumourigenesis [28,29]. In particular, previous studies have shown that ACSS2 can promote brain carcinogenesis by increasing the expression of autophagy-related factors, such as LAMP1.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%